Identification of Cryptococcus sp., through the Auxonogram Method Modified by Araujo - Celina Pérez; Yumaira Hernández; María Teresa Colella; Arantza Roselló; Claudia Hartung de Capriles; Carolina Olaizola; Sylvia Magaldi; Sofía Mata-Essayag (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2004)
Identification of 43 C. neoformans isolates from human sources were performed using the Beijerinck auxonogram method modified by Araujo and the MicroScan® DADE BEHRING automatic test. Identification of the isolates was achieved reliably by both tests. Therefore the Araujo Auxonogram method may be applied in small laboratories with limited resources as an inexpensive, simple and reliable method.